Khronika dnia . Khronika dnia . Chronicle of the Day . Хроника дня - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Episodes from the Moscow revolt; head of the commission on citizenship questions under the President of the Russian Federation, Abdulas Mikitaev, comments on the situation. Contributors: Torchinskii, Sergei (Anchor) Сцены мятежа в Москве; председатель комиссии по вопросам гражданства при президенте Российской Федерации, Абдулас Микитаев, комментирует ситуацию. Создатели: Торчинский, Сергей (Ведущий/Ведущая)